Valoración productiva del cultivo de maíz (Zea mays l.), variedad INIAP-111, a la aplicación de franjas ricas de nitrógeno en la localidad de Laguacoto III, provincia Bolívar - Méjico Camacho, Mayra Elizabeth (2022)
Corn ranks third in world production, after wheat and rice, with an area of 106 million ha, and an average yield of 2 T/ha. In the Andean zone of Ecuador, located between 2000 and 3000 meters above sea level, yields are approximately 0.68 T/ha, covering an estimated area of 148233 ha. The province of Bolívar occupies a large part of its territory in the cultivation of soft corn and contributes 26% of the total production of this cereal at the national level. Approximately 38,000 ha are cultivated. Obtaining high-yielding crops is related to the efficient use of fertilizers. Nitrogen fertilization is essential for crop yields, considering also the cost-benefit ratio and the environmental problems involved in contaminating water with nitrates. N increases the growth rate of the crop, strengthens flowering and fertilization, and is directly associated with the number of grains per ear. Nitrogen is one of the essential nutrients that limits corn yield. This research was carried out in the agroecological zone of Laguacoto III at 2622 meters above sea level. The objectives were: i) Compile data on the agronomic characteristics of the corn crop, identified in the UEB Research Platform 2020 -2021 ii) Determine the chemical and productive efficiency in the corn crop for this agroecological zone iii) Establish the economic cost-benefit analysis of the different treatments. A simple Randomized Complete Block Design with three replications was applied. The factor under study was the dose of nitrogen fertilization applied to the soil, which corresponded to six treatments: T1: Urea: 93 kg N/ha; T2: Urea: 147 kg N/ha; T3: Urea: 195 kg N/ha; T4: Urea: 244 kg N/ha; T5: Ecoabonaza: 110 kg N/ha and T6: Control: 0 kg N/ha. The main yield components were evaluated and analysis of variance, Tukey's test at 5%, correlation, regression and economic analysis were performed. There was a different effect of nitrogen fertilization levels on the yield of soft corn, i.e. the higher the N dose, the higher the yield. The highest average yields were determined in treatments T4 and T2 with 5189.40 and 5142.50 kg/ha, respectively. The components that increased corn yield were: ear length, stalk diameter, corn yield in bags per hectare, yield in kilograms per plot and percentage of plants with two ears. However, economically, T2 reported a net benefit of $ 1634.74, which means that for each dollar invested, the producer earns $ 0.90. Finally, this research allowed validating nitrogen fertilization levels as an alternative to increase the productive potential of the soft corn crop. It is recommended as an alternative to increase yields, the incorporation of Urea with the addition of 244 kg/ha of N to improve the agronomic components of soft corn INIAP-111, according to the agroecological zone in which it will be grown to contribute to food security.